(untitled) (REMUNOM, 2025)
Organic and intercropped vegetable production systems represent sustainable alternatives that reconcile economic viability, environmental benefits, and positive social impacts. This study aims to identify the challenges and potentialities of organic and intercropped systems in vegetable production from a socioeconomic and environmental perspective. The adoption of organic and intercropped practices faces obstacles such as the need for more intensive management, higher demand for technical knowledge, and commercialization limitations. However, these challenges are counterbalanced by advantages such as reduced use of agrochemicals, improved soil quality, diversified production, and higher market value of products. Additionally, these systems contribute to food security and environmental conservation by promoting biodiversity and reducing the degradation of natural resources. The research highlights the importance of public policy incentives and farmer training to expand the adoption of these practices. It is concluded that, despite the difficulties, organic and intercropped systems have great potential to make vegetable production more sustainable and economically viable.